The challenging management of malignant ureteral obstruction: Analysis of a series of 188 cases - Alberto Artiles Medina; Inés Laso García; Fernando González Tello; Sara Álvarez Rodríguez; Manuel Hevia Palacios; Marina Mata Alcaraz; César Mínguez Ojeda; Fernando Arias Funez; Victoria Gómez Dos Santos; Francisco Javier Burgos Revilla (Current Urology)
Abstract. Background. Malignant ureteral obstruction (MUO) is a common condition that complicates the course of advanced malignancies. The aims of this study are to analyze the causes, management, and survival of patients with obstructive nephropathy due to malignant ureteric obstruction and to determine prognostic factors. Furthermore, we studied the complications and outcomes in patients who underwent urinary diversion. Materials and methods. A retrospective study was conducted on patients with computed tomography–confirmed MUO between January 2016 and November 2020. Demographic, clinical, radiological, laboratory, and management data were collected. Survival curves were estimated using the Kaplan-Meier method, and univariate and multivariate Cox proportional hazards models were used to test the association between parameters and survival. Results. A total of 188 patients were included. The mean age was 69.01 years (SD, 14.95 years), and the majority (54.8%) were male. The most common mechanism leading to MUO was compression by a pelvic mass (36.9%), and the 3 most frequent tumors causing MUO were prostate (17.6%), bladder (16.5%), and rectal cancer (11.7%). Forty-seven patients (25%) underwent urinary diversion: 23 (48.9%) underwent double-J stenting and 21 (44.7%) underwent percutaneous nephrostomy. The most common reason for urinary diversion was acute kidney injury (53.3%). Recovery of renal function was observed in 55.8% of the patients after urinary diversion. The most frequently identified complications after urinary diversion were urinary tract infection (24.4%), hematuria (17.0%), and urinary sepsis (14.9%). The median survival after hydronephrosis diagnosis was 6.43 months (interquartile range, 1.91–14.81 months). In patients who underwent urinary decompression, the median survival after urinary diversion was 8.67 months (interquartile range, 2.99–17.28 months). In the multivariate analysis, a lower grade of hydronephrosis and cancer cachexia negatively impacted survival. Conclusions. Cancer patients with MUO have a poor prognosis; therefore, the risk-benefit ratio of urinary diversion should be carefully considered. Cachexia and hydronephrosis grade can be useful in selecting suitable candidates for urinary diversion.